Application of Instagram Media for ‘No Club’ Business Growth - Noni Yanti; Liliana Dewi (Fakultas Bisnis, 2021)
Instagram is one of the most popular social media right now. This is proven by millions of active users who use it. In order to optimize Instagram marketing, research is done on well-known brands in Surabaya that use Instagram as their marketing media. The aim of this research is to explore more about which marketing techniques are more effective than others among Instagram business owners, so that it can be used by researcher to determine Instagram marketing optimization efforts for No Club business growth. The method used in this research is qualitative research using descriptive analysis. The informants in this study were three people who were selected based on purposive sampling. Observation and interview were conducted on brands in Surabaya who use Instagram as their marketing media, namely Other Rag Enterprise, Cosmic, and Garlick. The results of this study indicate that Instagram is effectively used for marketing activities. There are several strategies that can be implicated by No Club related to features on Instagram such as cameras, hashtags, arrobas, geotagging, and comments also need to be considered to improve service quality. The most effective marketing on Instagram is by soft selling and up to date every day with at least 1 post a day and a simple but attractive caption. Promotion can be carried out with selebgram and those who are still relevant to the young and fashion target market. The focus of the promotion is on the Instagram feeds and Instagram story features.